Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0220
|View full text |Cite
|
Sign up to set email alerts
|

Gold–Thiol Self‐Assembled Monolayers

Abstract: Introduction Analytical Tools for Monolayer Characterization Preparation of Gold–Thiol Monolayers Structure of Gold–Thiol Monolayers Stability of Monolayers Chemical Reactions in Monolayers Non‐Covalent Interactions of Monolayers with Guest Molecules Thiol Monolayers on the Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 545 publications
0
1
0
Order By: Relevance
“…These properties can be used for specific and non-specific binding of biomolecules and nanoparticles and, therefore, can serve as useful templates for nano- and micro-fabrication. The first systematic study of thiol chemicals was reported by Zisman and co-authors [ 1 ], and has since been investigated by many researchers, including a detailed review by Chechik et al [ 2 ]. SAMs can be defined as "molecular assemblies that are formed spontaneously be the immersion of an appropriate substrate into a solution of an active surfactant in an organic solvent" [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties can be used for specific and non-specific binding of biomolecules and nanoparticles and, therefore, can serve as useful templates for nano- and micro-fabrication. The first systematic study of thiol chemicals was reported by Zisman and co-authors [ 1 ], and has since been investigated by many researchers, including a detailed review by Chechik et al [ 2 ]. SAMs can be defined as "molecular assemblies that are formed spontaneously be the immersion of an appropriate substrate into a solution of an active surfactant in an organic solvent" [ 3 ].…”
Section: Introductionmentioning
confidence: 99%